Catalysts based on Ni-Fe oxides supported on γ-Al2O3 for the oxidative dehydrogenation of ethane - Hurtado Cotillo M. (2020)
Catalysts based on Ni-Fe-a with a catalyst ratio of a = Ni/(Ni + Fe) (a = 0.8 and 0.9) supported on γ-Al2O3 were prepared by coprecipitation-deposition and tested for the oxidative dehydrogenation (ODH) of ethane. The bulk mixed samples exhibited 30% greater selectivity toward ethylene than did the corresponding simple oxide NiO. Meanwhile, the most selective sample, NiFe-0.9/γ-Al2O3, achieved a maximum of 94% at 400 °C. The remarkable selectivity of NiFe-0.9/γ-Al2O3 was attributed to the partial substitution effect of Ni2+ by Fe3+, thus allowing those catalysts to form oxygen sites that are specific for the partial oxidation of ethane to ethylene. Some additional factors that could have contributed to ethylene selectivity were the formation of low-reducibility species with controlled particle size, a better dispersion of the active phase over the support and the synergy of Fe3+ with Ni2+ species promoted by metal-support interactions. Finally, the catalyst NiFe-0.9/γ-Al2O3 presented stability of 10 h of time-on-stream while maintaining an ethylene selectivity of approximately 60%. © 2019 Elsevier B.V.